2021
DOI: 10.5650/jos.ess20212
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Supplementation with EPA-enriched Phosphatidylcholine and Phosphatidylethanolamine on Glycerophospholipid Profile in Cerebral Cortex of SAMP8 Mice fed with High-fat Diet

Abstract: The destruction of lipid homeostasis is associated with nervous system diseases such as Alzheimer's disease (AD). It has been reported that dietary EPA-enriched phosphatidylcholine (EPA-PC) and phosphatidylethanolamine (EPA-PE) could improve brain function. However, it was unclear that whether EPA-PC and EPA-PE intervention could change the lipid composition of cerebral cortex in AD mice. All the senescence-accelerated mouse-prone 8 (SAMP8) mice were fed with a high-fat diet for 8 weeks. After another 8 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…PE (18:0/20:4) is one of the important components in major organs of human body, accounting for 30% of the PE in the kidneys and liver, 30% of the PE in the heart, and 10% of the PE in the brain . An in vivo study showed that ingestion of EPA-PL-containing PE (18:0/20:4) can increase the PE (18:0/20:4) in the cerebral cortex of mice, suggesting its potential effect on lipid homeostasis regulation and brain development . Similarly, Ding et al reported that EPA-PL taken orally significantly increased the PE (P-18:0/20:4) content in plasma and regulated fatty acid metabolic process in high-fat diet-induced obese mice, suggesting an important role for PE (P-18:0/20:4) in lipid metabolism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PE (18:0/20:4) is one of the important components in major organs of human body, accounting for 30% of the PE in the kidneys and liver, 30% of the PE in the heart, and 10% of the PE in the brain . An in vivo study showed that ingestion of EPA-PL-containing PE (18:0/20:4) can increase the PE (18:0/20:4) in the cerebral cortex of mice, suggesting its potential effect on lipid homeostasis regulation and brain development . Similarly, Ding et al reported that EPA-PL taken orally significantly increased the PE (P-18:0/20:4) content in plasma and regulated fatty acid metabolic process in high-fat diet-induced obese mice, suggesting an important role for PE (P-18:0/20:4) in lipid metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…49 An in vivo study showed that ingestion of EPA-PL-containing PE (18:0/20:4) can increase the PE (18:0/20:4) in the cerebral cortex of mice, suggesting its potential effect on lipid homeostasis regulation and brain development. 50 Similarly, Ding et al 51 reported that EPA-PL taken orally significantly increased the PE (P-18:0/20:4) content in plasma and regulated fatty acid metabolic process in high-fat diet-induced obese mice, suggesting an important role for PE (P-18:0/20:4) in lipid metabolism. The abundance of EPA and ARA-PL in WCB was significantly higher (P < 0.05) than those in BAW, while DHA-PL was enriched in BRW.…”
Section: Compositions Of Major Plmentioning
confidence: 96%
“…In our previous study, we found that there was no significant difference in the DHA content in the cerebral cortex of mice between the two groups after supplementation with EPA-PC and EPA-PE. 14 This suggested that the different polar heads of PC and PE might have a limited effect on the DHA supplementation in the brain. From our current results, EPA-pPE showed a different supplementary effect from EPA-enriched phospholipids without a vinyl ether linkage.…”
Section: Resultsmentioning
confidence: 99%
“…13 However, there was no obvious effect on the content of polyunsaturated fatty acids (PUFAs) in each phospholipid molecular species except to decrease the level of docosapentaenoic acid (DPA) in phosphatidylserine (PS) as well as increase the levels of arachidonic acid (AA) in PE and PS in the cerebral cortex of SAMP8 mice after supplementation of EPA-PC/PE. 14 Notably, in many types of seafood, such as shellfish and sea cucumbers, PE mainly exists in the form of plasmalogen that contains a vinyl ether linkage at the sn-1 position rather than an ester bond. 15 More importantly, EPA-enriched ethanolamine plasmalogen (EPA-pPE) played a greater role than EPA-PE in improving the number of neuron nissl bodies, increasing the density of dendritic cells and dendritic spines of cortical neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al [ 4 ] have found that DHA-enriched diet could increase species of n-3 polyunsaturated fatty acid (n-3 PUFA) and decrease n-6 polyunsaturated fatty acid (n-6 PUFA) in all major phospholipid classes stored in the hippocampus, including PC, diacyl-phosphatidylethanolamine (dPE), alkenylacyl-phosphatidylethanolamine or phosphatidylethanolamine plasmalogen (PE-pl), phosphatidylinositol (PI) and PS. Evidence showed that eicosapentaenoic acid (EPA)-enriched PC and PE could restore lipid homeostasis in dementia mice, dietary EPA-PC and EPA-PE could increase the amount of choline plasmalogen, lysophosphatidylethanolamine (LPE), arachidonic acid (AA)-containing PE and PS as well as decrease docosapentaenoic acid (DPA)-containing PS in the cerebral cortex of senescence accelerated mouse prone-8 mice fed with HFD [ 5 ]. It has been reported that HFD elevated most kinds of lipids such as diacylglycerol lysophosphatidylserine and ceramide (Cer) in brain regions while PS species were decreased, the changes played a role in insulin resistance and oxidative stress [ 6 ].…”
Section: Introductionmentioning
confidence: 99%